The Great Crash and the Onset of the Great Depression - Romer, Christina D. (Quarterly Journal of Economics, 1990)
This paper argues that the collapse of stock prices in October 1929 generated temporary uncertainty about future income which led consumers to forgo purchases of durable goods. That the Great Crash generated uncertainty is evidenced by the decline in surety expressed by contemporary forecasters. That this uncertainty affected consumer behavior is shown by the fact that spending on consumer durables declined drastically in late 1929, while spending on perishable goods rose slightly. This effect is confirmed by the fact that there is a significant negative relationship between stock market variability and the production of consumer durables in the prewar era. "Uncertainty is worse than knowing the truth, no matter how bad"